An actualized catalogue of the Psychodidae (Diptera) of Mexico and their known distribution by state - Ibáñez-Bernal, Sergio; Durán-Luz, Juana (Zootaxa, 2022)
A catalogue of Psychodidae of Mexico is presented. A total of 99 species in 30 genera of the subfamilies Bruchomyiinae, Phlebotominae, Psychodinae, and Trichomyiinae are listed, with bibliographic citations and distributional data by country and in the case of Mexico by states.